Generalists versus specialists in organizations - Ferreira, Daniel (2001)
In this paper, we discuss the trade-o¤ between specialization and coordination in an organizational design problem. Most papers on the assignment of heterogeneous managers to di¤erent hierarchic levels emphasize the role of talent: better managers should be on top of hierarchies. However, this requires talent to be measured on an one-dimensional scale. In this paper, we explore the implications of allowing talent to have two dimensions: breadth and depth. Specialists have deep knowledge of few areas while generalists have narrow knowledge of many areas. When perfect communication is impossible, hierarchies arise in which generalists are at the top and specialists are at the bottom. We propose a model of imperfect communication and discuss its implications for organizational design, the optimal degree of centralization and the depth of hierarchies. We show that our model also implies plausible organizational structures, like balanced hierarchies and pyramidal structures.